Akibat Hukum Perjanjian Al-Khalaf Al-Khash dalam Praktik Jual Beli Sepeda Motor dengan Sistem Indent - Winih, Titik Sri; Hanifuddin, Iza (Fakultas Syariah INSURI Ponorogo, 2023)
Along with the number of dealers standing in Ponorogo district. In this context, MPM Ponorogo dealers provide various facilities and conveniences to the community, so that this convenience makes the lower middle class interested in owning a motorcycle with purchases on credit or cash. In this case, the purchase of a motorcycle with an indent system is in great demand by the public because of the easy indent requirements by paying a down payment of less than 1,000,000 can already carry a motorcycle. The purpose of this study is to find out how the legal consequences of agreements with the indent system. The research method used is to use qualitative methods, using descriptive analysis methods. The legal consequences in the practice of buying and selling motorcycles with an indent system are contained in article 1338 of the Civil Code paragraphs (1), (2), (3), while the seller's obligation in delivering goods to the buyer is contained in article 1417 of the Civil Code. And for the validity of data in the practice of buying and selling motorcycles with an indent system, it has also been regulated in article 1320 of the Civil Code, which is one of the conditions for the validity of the agreement.